2012
DOI: 10.3390/ijms131114251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of β-Cyclodextrin Complexation on Solubility and Enzymatic Conversion of Naringin

Abstract: In the present paper, the effect of β-cyclodextrin (β-CD) inclusion complexation on the solubility and enzymatic hydrolysis of naringin was investigated. The inclusion complex of naringin/β-CD at the molar ratio of 1:1 was obtained by the dropping method and was characterized by differential scanning calorimetry. The solubility of naringin complexes in water at 37 ± 0.1 °C was 15 times greater than that of free naringin. Snailase-involved hydrolysis conditions were tested for the bioconversion of naringin into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…It has been reported to possess antiapoptotic, antiosteoporosis, antiulcer, antioxidant, antiinflammatory, and anticarcinogenic properties (13-14). Emerging data indicate that naringin is involved in amelioration of hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported to possess antiapoptotic, antiosteoporosis, antiulcer, antioxidant, antiinflammatory, and anticarcinogenic properties (13-14). Emerging data indicate that naringin is involved in amelioration of hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent epidemiological and dietary interventional studies, both in humans and animals, suggest that these flavonoids prevent and delay neurodegeneration, especially in aged-population cognitive dysfunction [9]. Naringin (Figure 1), a well-known flavanone glycoside of Citrus fruits, possesses antioxidant, anti-inflammatory, anti-apoptotic, anti-ulcer, anti-osteoporosis and anti-carcinogenic properties [10,11]. Naringin has been reported to attenuate behavioral alterations and cognitive impairment in kainic acid-induced epilepsy models [12] and 3-nitropropionic acid-induced Huntington models [13].…”
Section: Introductionmentioning
confidence: 99%
“…There are studies that have found that the solubility of naringin is poor, which leads to low bioavailability and hinders further studies on its pharmacological actions [1]. At present, many investigations have sought to find some ways to increase the solubility of naringin to improve its bioavailability, which include the synthesis of naringin inclusion complexes, for instance, beta-cyclodextrin (β-CD) complexation could significantly increase the solubility of naringin [2], adding the flavonoids as a compatibilizer [3], and the preparation of an appropriate dosage form such as solid dispersion [4].…”
Section: Introductionmentioning
confidence: 98%